PACS2001. Proceedings of the 2001 Particle Accelerator Conference (Cat. No.01CH37268)
DOI: 10.1109/pac.2001.988297
|View full text |Cite
|
Sign up to set email alerts
|

Funneling with the two-beam RFQ

Abstract: By ion beam funneling the beam current can be multiplied without changing the emittance, which is proposed for new high current accelerator facilities like HIDIF or ESS. There the required beam current can not be produced by a single pass rf-linac. The increase in brightness in such a driver linac is done by several funneling stages at low energies, in which two identically funneling studies, are not necessary [1,2,3]. A short r.f. funneling deflector is placed at the beam crossing position behind the RFQ. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The emittance from the beamline with the matching section reduces the beam radius. The measurements are in good agreement with our simulations shown in figure 8 shown that funneling can be done [7,9], but the beams…”
Section: Beam Testssupporting
confidence: 89%
See 1 more Smart Citation
“…The emittance from the beamline with the matching section reduces the beam radius. The measurements are in good agreement with our simulations shown in figure 8 shown that funneling can be done [7,9], but the beams…”
Section: Beam Testssupporting
confidence: 89%
“…For beam bending to a common axis we use two types of deflectors, the single and the multi cell funnel deflector [7]. The multi cell deflector allows beam bending at lower voltages in the bending gap.…”
Section: Multi Cell Deflectormentioning
confidence: 99%
“…The Frankfurt Funneling Experiment consists of two multicusp ion sources, a Two-Beam RFQ accelerator and a funneling deflector to bend both beam lines to a common beam axis [1,2]. The principle of funneling is displayed in fig.…”
Section: Introductionmentioning
confidence: 99%